Moving beyond attendance: Lessons learned from assessing engagement in afterschool contexts. Issue 144 (December 2014) - Fredricks, Jennifer A.; Bohnert, Amy M.; Burdette, Kimberly
Abstract : Youth engagement is the least researched, but potentially most important, aspect of participation in afterschool programs. The level of youth engagement can vary across programs, across youth within a program, and within individual youth over time. Engagement is important for both recruiting and retaining participants, and has been associated with more positive academic outcomes over time. This chapter integrates perspectives from practitioners, researchers, and the school engagement literature. Reasons why engagement is an important dimension of afterschool programming, different methods for assessing engagement, key features of engaging afterschool programs, and implications for practice are also outlined.